Casa Cuadrau : yoga, art, and nature in the Spanish Pyrenees - Reddy, Roopa, (SAGE Knowledge. Cases., 2019)
Casa Cuadrau is a yoga retreat center in the Spanish Pyrenees. It is the result of a dream that both of its founders, Dani and Katya, had for many years. In December 2013, after the first full season of operation, Dani and Katya are considering where they should focus their marketing efforts for the next year. They are worn out, but can't afford to hire additional staff without increasing revenues. They feel that there are many possible marketing alternatives, but are not sure which is the best direction to take.